The Israelites in Scroll (A) of the Damascus Document: A Comparative Study Between the Holy Qur’an and the Bible - Bani Abdul Rahman, Raed Saeed; Shakhatrah, Susan Rakan (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This research discusses the Damascus Document, which was discovered at the end of the 19th century. It presents part of the first section of its contents, specifically scroll (A) related to the Israelites, introduces and analyzes this content, highlights the most important issues mentioned in the document, and identifies intersections with the Quran and the Bible. It compares the findings among the three sources. Methods: The study used the inductive method by examining texts related to the Israelites in scroll (A) of the Damascus Document. They also employed the analytical method based on the content of these texts and the comparative method between the contents of the Damascus Document and those of the Quran and the Bible. Results: The events and occurrences mentioned in scroll (A) of the Damascus Document concerning the Israelites align with many events mentioned in the Quran and the Bible. This indicates that the Damascus Document contains a significant portion of prophetic revelation and may indeed be remnants of the true Torah and Gospel. Conclusion: The study recommends giving more attention to the Damascus Document, further researching these valuable sources, and re-studying them in light of the Quranic text and the Hadith of the Prophet.